2011
DOI: 10.1080/00224545.2010.503721
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to Women's Crime: Differences Among Women Convicted of Drug, Violence and Fraud Offenses

Abstract: The current study was conducted on 60 Israeli female inmates. Our aim was to examine the differences among women convicted for drug, violence, and fraud offenses by socio-demographic variables and self-control and aggression levels. Results revealed that the drug group was characterized by measures attributed to chronic delinquency, and the fraud group was found to fit the pathway to low crime. At the same time, the violence group was not characterized by any of these patterns. The findings were discussed in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 44 publications
1
21
0
2
Order By: Relevance
“…Around 6% to 10% of white-collar criminals have been abused or neglected as a child and around 6% to 10% have reported that they have one or more criminal family members or friends. However, this is significantly less than what street criminals report, which is around 17% to 20% reporting abuse or neglect and 18% to 20% having a criminal family member or friend (Benson, 2002;Kerley & Copes, 2004; see also Shechory et al, 2011).…”
Section: Demographymentioning
confidence: 96%
See 2 more Smart Citations
“…Around 6% to 10% of white-collar criminals have been abused or neglected as a child and around 6% to 10% have reported that they have one or more criminal family members or friends. However, this is significantly less than what street criminals report, which is around 17% to 20% reporting abuse or neglect and 18% to 20% having a criminal family member or friend (Benson, 2002;Kerley & Copes, 2004; see also Shechory et al, 2011).…”
Section: Demographymentioning
confidence: 96%
“…However, this research has begun to expand beyond its historical concentration in Anglo-American countries (the US and the UK) by extending quantitative and qualitative data sampling to several other countries, including Germany (Blickle, et al, 2006;Cleff, 2013), Austria (Noll, 2014), the Netherlands (Onna et al, 2014), Italy (Merzagora, et al, 2014), Sweden (Alalehto & Larsson, 2008, 2012Ring, 2003;Kardell & Bergqvist, 2009), Norway (Gottschalk, 2013;Gottschalk & Glasø, 2013), Finland (Häkkänen-Nyholm & Nyholm, 2012Kankaanranta & Muttilainen, 2010), Israel (Shechory et al, 2011), Australia (Freiberg, 1992;Duffield & Grabosky, 2001), Canada (Gagnon, 2008;Ouimet, 2011;Paquette, 2010), and China (Deng, Zhang, & Leverentz, 2010). But, of course, much of the research has still been performed in the UK (e.g.…”
Section: White-collar Crime: a Global Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…We do know that there are some specific bad environmental conditions which correlate with white collar criminality on the individual level. Those are a higher divorce rate than among street criminals and the general population (Alalehto & Larsson, 2008;Klenowski, Copes, & Mullins, 2010;Walters & Geyer, 2004;Weisburd, 1991), especially among female white collar offenders (Daly, 1989;Haantz, 2002;Shechory, Perry, & Addad, 2011;Zukowski, 2015). And suffering from at least one emotional, marital, or substance abuse problem over the course of their lives (Weisburd, 1991;Soothill et al, 2012;Zukowski, 2015).…”
Section: The Gene-environment Associationmentioning
confidence: 99%
“…Based on the constructed life histories of 80 men and women felony offenders, Daly [10], in her seminal work, identified five prototypical pathways: street women-escape and survival, involving women fleeing abuse and engaging in survival strategies such as prostitution, theft, and drugs; drugconnected women, describing the use and trafficking of drugs by women in concert with romantic partners/family; harmed and harming women, involving offenders who have experienced traumatic abuse which led to their chronic criminality and violence; battered women, categorizing women whose crime is directly linked to their extreme victimization by their romantic partners; and other, entailing women whose crimes were economic-motivated. Building on such typologies, other pathways scholars have also specified similar trajectories and characterized them according to childhood victimization [6], abusive homes and gender oppression [13], extreme economic and racial marginalization [34,35], normal-functioning with drug-dependence [7,19,40], adult relationship dysfunction [37], socialized subculture, and anti-social aggression, resulting from extensive experiences of deprivation, trauma, hostility, and relationship issues [7].…”
Section: Pathways Perspective and Girls' Delinquencymentioning
confidence: 99%